2020
DOI: 10.5535/arm.2020.44.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Aerobic Capacity Over Time in Elderly Patients With Acute Myocardial Infarction During Cardiac Rehabilitation

Abstract: Objective To test the hypothesis that a longer duration of phase II cardiac rehabilitation is required to recover the exercise capacity of elderly patients compared to younger patients. Methods We retrospectively reviewed and analyzed the medical records of patients who were referred to our cardiac rehabilitation (CR) center and underwent percutaneous coronary intervention for acute myocardial infarction (AMI). A total of 70 patients were enrolled who underwent an exercise tolerance test (ETT) 3 weeks after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…5,6 Exercise outcomes from CR can vary substantially, which may be related to both patient and CR program factors. For instance, patient age 7 and sex 8 are known to independently contribute to variations in exercise capacity outcomes, as is the presence of metabolic, musculoskeletal, and respiratory comorbidities, 9 and psychological symptoms such as anxiety and depression. 10 Furthermore, ethnic minority status 11 and exercise capacity levels at CR entry may also influence improvement rate.…”
mentioning
confidence: 99%
“…5,6 Exercise outcomes from CR can vary substantially, which may be related to both patient and CR program factors. For instance, patient age 7 and sex 8 are known to independently contribute to variations in exercise capacity outcomes, as is the presence of metabolic, musculoskeletal, and respiratory comorbidities, 9 and psychological symptoms such as anxiety and depression. 10 Furthermore, ethnic minority status 11 and exercise capacity levels at CR entry may also influence improvement rate.…”
mentioning
confidence: 99%
“…Although a lot of studies are currently being conducted, authors use different physical exercise programs in an effort to find out the best one: of what intensity, frequency, and duration the CR should be and what type of exercises are most suitable for elderly patients. A recent study by Kim et al, published in 2020, reported that elderly patients needed CR of a longer duration than their younger counterparts: younger patients (<65 years) with acute myocardial infarction who had CR sessions 3 times a week showed an improvement in CPET parameters after 6 weeks, meanwhile in elderly patients (≥65 years), CPET parameters improved only after 12 weeks [ 23 ]. Other study showed a positive impact of a two month CR, given five times a week, on physical parameters such as 6MWD and VO 2 in all age groups, even in very old (≥80 years) patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…An additional decade in age was related to a reduced recovery in peak VO 2 by 1.1 ml/kg/min, while in non-surgery patients the reduction was only 0.4 ml/kg/min, suggesting that older age may not only reduce the effect of a physical training stimulus but also have an adverse effect on the healing process from surgery [ 22 ]. A previous study on patients undergoing CR has found older age to be a negative predictor for improvement in CRF [ 9 ], and another study found a smaller increase in CRF in elderly compared to younger patients [ 23 ]. However, other studies have found similar or even greater improvements in peak VO 2 with increasing age [ 24 ].…”
Section: Discussionmentioning
confidence: 99%